Efektivitas Penggunaan Alat Peraga Kartu Bilangan Untuk Meningkatkan Hasil Belajar Siswa Kelas II SD Dalam Memahami Lambang Bilangan - Maarif, Samsul (Universitas Sebelas Maret, 2020)
The use of the Number Card teaching aid in Class II SDN Kubangsari 01, in general, has the aim of improving student learning outcomes in MTK mupel in writing number symbols up to 900. The research method used is experimental technique. Based on the experimental results of the average student learning outcomes before being given treatment in the form of learning using number card props, the average value of these students (pretest) was only 50.33 and after being given treatment in the form of learning using number card props the average value The average of these students (posttest) became 75.00 with a KKM of 60. This result means that the use of the Number Card teaching aids can improve the learning outcomes of MTK mupel students, especially the number symbol material in Class II SDN Kubangsari 01.